KOMPARASI TINGKAT KEANEKARAGAMAN JENIS IKAN PADA PERAIRAN MANGROVE DAN TAMBAK TRADISIONAL DI SEKITAR PERAIRAN JUATA LAUT KOTA TARAKAN KALIMANTAN UTARA - Wiharyanto, Dhimas; Salim, Gazali (Jurnal Harpodon Borneo, 2014)
Estuaries or also known as ustuaria is the area of water bodies into a meeting between one or more rivers in coastal areas with marine areas. Juata Laut waters located in the northern part of Tarakan Island. These waters are a small part of the estuarine waters in this region, which connects the river Sesayap which is one of the major rivers located in the northern coastal region of North Kalimantan with the surrounding sea area. The purpose of this study was to determine the type and level comparison fishes diversity found in mangrove waters and traditional farms around the waters of Juata Laut Tarakan City North Kalimantan province. Types of fish found in the waters of the Sea of mangrove Juata as many as 23 types, while in pond waters around 19 species. Level of biodiversity of fish in mangrove waters and traditional farms around the waters of the Sea Juata classified in the spring rate which means it has a lower level of community stability. Keywords : Comparation, diversity, fishes.